Resource Partitioning of Sympatric African Wolves (Canis lupaster) and Side-Striped Jackals (Canis adustus) in an Arid Environment from West Africa - Maria João Paúl; Jorge F. Layna; Pedro Monterroso; Francisco Álvares (Diversity, 2020)
Knowledge on interference competition between species, particularly for scarce crucial resources, such as water, is a topic of increasing relevance for wildlife management given climate change scenarios. This study focuses on two sympatric canids, the African wolf and the side-striped jackal, to evaluate their group size and spatiotemporal activity patterns in the use of a limited resource by monitoring artificial waterholes in a semi-arid environment located in Senegal (West Africa). Remote cameras were deployed at five artificial waterholes to evaluate the number of individuals, age and activity patterns of resource use. African wolves (n = 71; 31% of all carnivore detections) and side-striped jackals (n = 104; 45%) were the most detected carnivore species. While both canids tended to occur alone at waterholes, they showed an evident monthly variation in group size. Both species showed a high activity overlap, with a bimodal activity pattern in waterhole use. However, we found evidence of unidirectional spatiotemporal avoidance, suggesting African wolves might be dominant over side-striped jackals. Our findings provide useful insights to investigate niche partitioning on the use of limited resources and have conservation implications for regions with a prolonged dry season.